2021
DOI: 10.3389/fpubh.2021.724398
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 Infection in the Colombo Municipality Region, Sri Lanka

Abstract: Background: As the Municipality Council area in Colombo (CMC) experienced the highest number of cases until the end of January 2021, in Sri Lanka, we carried out a serosurvey prior to initiation of the vaccination program to understand the extent of the SARS-CoV-2 outbreak.Methods: SARS-CoV-2 seropositivity was determined in 2,547 individuals between the ages of 10–86 years, by the Wantai total antibody ELISA. We also compared seroprevalence using the haemagglutination test (HAT) to evaluate its usefulness in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The Wantai ELISA assay was shown to have a sensitivity of 98% [ 11 ]. It was also found to be 100% specific when tested in over 100 serum samples obtained in year 2018, in Sri Lankan individuals [ 12 ]. The assay was carried out and results were interpreted according to manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The Wantai ELISA assay was shown to have a sensitivity of 98% [ 11 ]. It was also found to be 100% specific when tested in over 100 serum samples obtained in year 2018, in Sri Lankan individuals [ 12 ]. The assay was carried out and results were interpreted according to manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The HAT was carried out as previously described using the BA.2.75 and XBB.1.5 versions of the IH4-RBD reagents with additional mutations in the RBD (Y365F, T392W and V395I) [22, 23]. The assays were carried out and interpreted as previously described by us and these assays have been used previously in serosurveys carried out in the Colombo district in Sri Lanka [16, 24]. The HAT assays were performed with sera at 1:40 and 1:80 dilutions, to determine presence of RBD-specific antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-COV-2 specific total antibody (IgM, IgG and IgA) responses were evaluated using the Wantai SARS-CoV-2 Ab ELISA (Beijing Wantai Biological Pharmacy Enterprise, China) as previously described. This assay has been used in carrying out serosurveys for SARS-CoV-2 previously in Sri Lanka, in the Colombo district [16]. This assay was shown to have a sensitivity of 98% [17] and was found to be 100% specific in serum samples obtained in 2018, in Sri Lankan individuals.…”
Section: Assays For Sars-cov-2 Specific Total Antibodies and Ace2 Blo...mentioning
confidence: 99%
“…These studies show that SARS-CoV-2 infections in children have been frequently underdiagnosed. 12 , 13 , 14 Many of these studies conducted in different countries before 15 , 16 , 17 , 18 and after vaccine availability 19 showed a lower number of infection-derived SARS-CoV-2 antibody detection in children compared to adults. However, country and regional study differences conducted at varying timepoints during the pandemic have reported mixed results.…”
Section: Introductionmentioning
confidence: 99%